Luteinizing hormone receptor gene and regulator of G-protein signaling 2 gene expression level and association with oocyte maturity in in vitro fertilization/intracytoplasmic sperm injection cycle - Thanik Chokjirawat; Mutchuporn Sukpresert; Wicharn Choktanasiri; Wanwisa Waiyaput; Duangporn Saengwimol; Aruchalean Taweewongsounton; Tanjitti Pongrujikorn; Chonthicha Satirapod (Wolters Kluwer Medknow Publications, 2018)
Aims: The aim is to study the relation and distribution in gene expression level of the luteinizing hormone receptor (LHR) gene and regulator of G-protein signaling 2 (RGS2) gene expression with oocyte maturation. Setting and Design: This cross-sectional study was undertaken in an instruction-based tertiary care infertility unit, department of obstetrics and gynecology. Materials and Methods: After controlled ovarian hyperstimulation, cumulus granulosa cells (CCs) from 59 oocytes among 18 women being treated by in vitro fertilization/intracytoplasmic sperm injection cycle technique from November 2015 to January 2016 were collected on the day of oocyte retrieval. Total RNA was extracted and converted to cDNA in individual oocytes. LHR and RGS2 gene levels were measured and analyzed using digital droplet polymerase chain reaction. Statistical Analysis: Gene expression level was analyzed using software STATA, version 14.0 (College Station, TX: StataCorp LP, USA). Results: CCs were obtained from 59 cumulus-oocyte complexes (COC), 46 COC from metaphase II (CCMII), 13 COC from metaphase I, and GV oocyte (CCMI + GV). The RGS2 gene expression level, when compared with the housekeeping gene in CCMIIand CCMI + GV, was 0.15 (0.05-0.52) and 0.08 (0.02-0.27), respectively. The LHR gene expression when compared with the housekeeping gene in CCMIIand CCMI + GVdid not differ and was quite in the same value that was 0.02 (0.00-0.11) and 0.02 (0.00-0.06), respectively. Conclusion: This study showed that LHR gene expression did not differ in between oocyte groups. Even though the median of RGS2 gene expression was more in the mature oocyte group, the result was inconclusive due to scattering and overlapping of gene expression data between oocyte groups.